Abhinavagupta's Commentary on the Bhagavad Gita = Gītārtha-saṁgraha - Marjanovic, Boris (Indica Books, 2004)
Classical commentary on Bhagavadgītā, Hindu philosophical classic; Includes Sanskrit text with English translation.